SAFETY EMERGENCY MANAGEMENT STRATEGY OF INDUSTRIAL BUILDING CONSTRUCTION PROJECTS: BASED ON ANALYSIS METHODS OF POLYMORPHIC FUZZY RELIABILITY - Bai, Xiaoping; Zhao, Jian (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Strengthening emergency management of construction safety accidents is an urgent problem. There are few researches on how to ensure emergency intervention to achieve low casualties and property losses after accidents. The paper presented a novel safety emergency management strategy of construction projects: based on analysis methods of polymorphic fuzzy reliability. In the research process, the emergency management and system reliability methods are integrated to build an accident tree analysis model for safety emergency management in construction projects, which is transformed into a polymorphic Bayesian network based on reliability. It makes up for the problem that it is difficult to describe the polymorphism of events and the indeterminacy of logic relations in fault tree analysis. The authors added the fuzzy set theory into the Bayesian network to determine the exact probability of different states of nodes, then the posterior probability and critical importance degree of each root node are calculated. Research result shows that integrating reliability theory with emergency management can improves the reliability of the entire system by analyzing the weak links of the Bayesian network system. The research can provide a reference for safety accident analysis in a multi-state complex system.